Induction of pro-inflammatory response of the placental trophoblast by Plasmodium falciparum infected erythrocytes and TNF (2013)
ABSTARCT: Plasmodium falciparum placental malaria is characterized by the sequestration of infected erythrocytes (IEs) in the placental intervillous space via adherence to chondroitin sulphate A (CSA), production of inflammatory molecules, and leukocytes infiltration. Previous reports suggest that the syncytiotrophoblast (ST) immunologically responds to IEs contact. This study explores the inflammatory response induced in BeWo cells by adherence of IEs and TNFstimulation. METHODS: A non-syncitialized BeWo cells (trophoblast model) were used to evaluate its response to CSA-adherents IEs (FCB1csa, FCB2csa, FCR3csa, 3D7csa) and TNF stimulation. Expression of membrane ICAM-1 (mICAM-1) receptor in BeWo cells was quantified by flow cytometry and the IL-8, IL-6 and soluble ICAM-1 (sICAM-1) concentrations were quantified by enzyme-linked immunosorbentassay (ELISA) in BeWo stimulated supernatants. RESULTS: BeWo cells stimulated with TNF and CSA-adherents IEs of FCB1csa and 3D7csa (strains with higher adhesion) increase the expression of ICAM-1 on the surface of cells and the secretion of immune factors IL-8, IL-6 and sICAM-1. This inflammatory response appears to be related to the level of adherence of IEs because less adherent strains do not induce significant changes. CONCLUSIONS: It was found that BeWo cells responds to CSA-IEs and to TNF favouring a placental pro-inflammatory environment, evidenced by increases in the expression of membrane mICAM-1 and release of soluble ICAM-1, as well as the IL-8 and IL-6 secretion. The expression of ICAM-1 in BeWo cells might be associated to an increase in leukocyte adhesion to the trophoblast barrier, promoting greater inflammation, while the sICAM-1 release could be a protection mechanism activated by trophoblastic cells, in order to regulate the local inflammatory response.